Pluralism and Dialectic: On James's Relation to Hegel. Issue 2 (4th September 2015) - Schultz, Lucy Christine
Abstract : In this paper James's pluralism is examined in light of his critiques of 'intellectualism' and monistic idealism in order to elucidate his relationship to Hegel. Contrary to the strong anti-Hegelianism found throughout the writings of James, Hegel's dialectic and speculative logic are able to give a rational account of the continuity of objects and relations within experience that James struggled to articulate in A Pluralistic Universe . Neither James nor Hegel is an absolute pluralist or monist due to the interdependence of the concepts of unity and plurality, aptly described by Hegel in his Logic, and alluded to by James in various places throughout his work. Thus, the ambiguity of the nature of James's pluralism previously noted by scholars is explained, and the relevance of Hegel and dialectic for pragmatist theory is elucidated.